Relevansi Monisme dan Dualisme Bagi Pemberlakuan Perjanjian Internasional di Indonesia - Intan Permata Putri; Rima Yuwana Yustikaningrum; Ananthia Ayu Devitasari (The Constitutional Court of the Republic of Indonesia, 2022)
The application of treaty is still influenced by different views on the approach chosen by Indonesia, whether monism or dualism. By using normative method, this study questions the relevance of monism-incorporation and dualism-transformation approaches in determining the application of treaty. Two key aspects will be reviewed, namely parliamentary approval and the drafting of national regulations to implement treaty. It concludes that the dichotomy of monism and dualism has various limitations, and is irrelevant for determining the application of treaty. Parliamentary approval is required for treaty application, both in monist and dualist countries. Several dualist countries have even sought parliamentary approval before ratification can take place. The formulation of national regulations is common in monist and dualist countries. Not to fulfill theoretical demands in line with the monism and dualism approaches, but to ensure harmonization and the ability of state to carry out its obligations.